Roles of Exosomes Derived From Immune Cells in Cardiovascular Diseases - Wu, Runda; Gao, Wei; Yao, Kang; Ge, Junbo (Frontiers in Immunology, 2019)
Therapies aimed at minimizing adverse remodeling in cardiovascular diseases on a molecular and cellular basis are urgently needed. Exosomes are nanosized lipid vesicles released from various cells that are able to mediate intercellular signaling and communication via their cargos. It has been increasingly demonstrated that exosomes from cardiomyocytes or stem/progenitor cells can promote cardiac repair and regeneration, but their mechanism has not been fully explained. Immune responses mediated by immune cells also play important and complicated roles in the progression of various cardiovascular diseases such as myocardial infarction and atherosclerosis. Exosomes derived from immune cells have shown pleiotropic effects on these pathological states, whether similar to or different from their parent cells. However, the underlying mechanism remains obscure. In this review, we first describe the biological characteristics and biogenesis of exosomes. Then we critically examine the emerging roles of exosomes in cardiovascular disease; the exosomes we focus on are derived from immune cells such as dendritic cells, macrophages, B cells, T cells, as well as neutrophils and mast cells. Among the cardiovascular diseases we discuss, we mainly focus on myocardial infarction and atherosclerosis. As active intercellular communicators, exosomes from immune cells may offer prospective diagnostic and therapeutic value in cardiovascular disease.